1990
DOI: 10.1017/s003118200006008x
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of cyclosporin A (CsA) against developmental stages of Schistosoma mansoni in mice

Abstract: It has been shown elsewhere that the immunosuppressive drug cyclosporin A (CsA) exerts profound schistosomicidal activity when given to infected mice via a multiple administration regime. We show here that a single treatment regime also effects significant reductions in worm burden. Moreover, drug efficacy is maintained at CsA concentrations shown to be subimmunosuppressive in other systems. Subcutaneous treatment effected higher levels of schistosomicidal activity than intraperitoneal or oral treatment, irres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…A large amount of information is available on the toxic effects and doses of the drug to be safely administered to humans. The drug is known to be anti-parasitic at subimmunosuppressive levels (Munro & McLaren, 1990 ;Page et al 1995) and is suggested to mediate it's effects through inhibition of normal parasite cyclophilin function. However, no direct association between the anti-parasitic effects of CsA and parasite cyclophilin has yet been established (Khattab et al 1998 ;McLauchlan et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A large amount of information is available on the toxic effects and doses of the drug to be safely administered to humans. The drug is known to be anti-parasitic at subimmunosuppressive levels (Munro & McLaren, 1990 ;Page et al 1995) and is suggested to mediate it's effects through inhibition of normal parasite cyclophilin function. However, no direct association between the anti-parasitic effects of CsA and parasite cyclophilin has yet been established (Khattab et al 1998 ;McLauchlan et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The observations in this study of the interaction between CsA and immune effector mechanisms employed an experimental heterologous transfer (rabbit to mouse) model which may not reflect the situation within the natural host. With respect to the immune-mediated elevated mortality rate of CsA-treated worms, it has been previously shown that host leucocytes will invade the morphologically compromised tegument of CsA-treated adult worms and this has been interpreted as the probable causal event in parasite elimination (Munro & McLaren 1990b).…”
Section: Discussionmentioning
confidence: 99%
“…An anti-schistosome effect of cyclosporin A (CsA) was first reported by Bueding et al (1981), and verified in subsequent studies (Bout et al, 1984;Kasinathan et al, 2011;Munro and McLaren, 1990). …”
Section: Chapter 5 -Conclusion and Future Directionsmentioning
confidence: 78%
“…However, the exact mechanism is still unknown and there have been various speculations on how CsA affects schistosomes (Bout et al, 1984;Guorlay et al, 2007;Kasinathan et al, 2011;Munro and McLaren, 1990), with the P-glycoprotein (P-gp) (an ATP-binding cassette (ABC) transporter) (Kasinathan et al, 2011) (2011), I showed that CsA disrupted egg production in schistosomes. Furthermore, I also found that worms treated with CsA also produce eggs that show delay in development and maturation.…”
Section: Discussionmentioning
confidence: 99%